The Palaeoproterozoic (∼2.06 Ga) Rooiberg Group, South Africa: Dominated by extremely high-grade lava-like and rheomorphic ignimbrites? New observations and lithofacies analysis. (July 2017) - Lenhardt, Nils; Masango, Samson M.; Jolayemi, Olutola O.; Lenhardt, Sukanya Z.; Peeters, Gert-Jan; Eriksson, Patrick G.
Abstract: The∼ 2.06 Ga Rooiberg Group of South Africa, related to the greater Bushveld Complex-forming event (Bushveld Large Igneous Province) appears to have been associated with some of the largest eruptions of silicic rocks in the Precambrian rock record. Despite extensive geochemical work that has been carried out on the voluminous silicic volcanic and intercalated sedimentary rocks, so far, a clear interpretation of the eruptional, transport and depositional mechanisms is still outstanding. In the north-eastern Loskop Dam area (Mpumalanga Province), ca. 120 km E of Pretoria, three of the four formations of the Rooiberg Group are exposed in the field. After extensive mapping, a lithofacies analysis was carried out in order to provide a detailed set of the lithofacies types that represent the Rooiberg Group. Seven lithofacies types are identified that can be grouped into syn-eruptive and inter-eruptive lithofacies associations, representing times of explosive eruptions, and times of relative quiescence and clastic sedimentation. The majority of the dacitic to rhyolitic rocks at Loskop Dam that have formerly been described as lavas, are now interpreted here as extremely high-grade lava-like and rheomorphic ignimbrites. The ignimbrites were the result of highly explosive eruptions with low eruption columns, probably originating from fissure eruptions that may have been related to one or more calderas. Highlights: First lithofacies analysis of the Palaeoproterozoic Rooiberg Group rocks NE of Loskop Dam, Mpumalanga, South Africa. New interpretation of the rocks as extremely high-grade lava-like and rheomorphic ignimbrites. The ignimbrites are the result of highly explosive eruptions with low eruption columns, probably originating from fissure eruptions.